2020
DOI: 10.5194/egusphere-egu2020-13107
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial control of carbon dynamics in soil by microbial decomposer communities

Abstract: <p>Trait-based models have improved the understanding and prediction of soil organic matter dynamics in terrestrial ecosystems. Microscopic observations and pore scale models are now increasingly used to quantify and elucidate the effects of soil heterogeneity on microbial processes. Combining both approaches provides a promising way to accurately capture spatial microbial-physicochemical interactions and to predict overall system behavior. The present study aims to quantify controls on carbon (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…They attributed this to the closer contact of OM with the soil aggregates where bacteria are located. For a uniform distribution of SOM, Pagel et al (2020) showed that a strong spatial clustering of microbial communities induced diffusionlimited C availability, which translated to lower decomposition degrees of C compounds. Pinheiro et al (2015) found that bacteria could not degrade the solute after a few weeks when initially separated in soil by a distance of 1.7 cm, although they could mineralize it when they were colocalized.…”
Section: Diffusion Lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…They attributed this to the closer contact of OM with the soil aggregates where bacteria are located. For a uniform distribution of SOM, Pagel et al (2020) showed that a strong spatial clustering of microbial communities induced diffusionlimited C availability, which translated to lower decomposition degrees of C compounds. Pinheiro et al (2015) found that bacteria could not degrade the solute after a few weeks when initially separated in soil by a distance of 1.7 cm, although they could mineralize it when they were colocalized.…”
Section: Diffusion Lengthmentioning
confidence: 99%
“…The distribution of the heterogeneity of minerals, pores, organic matter and microorganisms in soil occurs at fine scales of a few µm (Rawlins et al, 2016, Kravchenko and Guber, 2017. The access of microorganisms to macromolecular soil organic matter is dependent on the hydrolysis of organic molecules by exoenzymes and the diffusive transport of the resulting assimilable carbon in the soil solution from locations of exoenzymatic action to microorganisms (Pagel et al, 2020). The properties of the pore space, such as pore connectivity and tortuosity, affect the water distribution and consequently the diffusion pathways that may control the access of decomposers to organic substrates .…”
Section: Introductionmentioning
confidence: 99%